Bank liquidity creation and risk taking during distress - Allen N. Berger; Christa H. S. Bouwman; Thomas Kick; Klaus Schaeck (Deutsche Bundesbank, 2010)
Liquidity creation is one of banks' raisons d'être. But what happens to liquidity creation and risk taking when a bank is identified as distressed by regulatory bodies and subjected to regulatory interventions and/or receives capital injections? What are the long-run effects of such interventions? To address these questions, we exploit a unique dataset of German universal banks for the period 1999 - 2008. Our main findings are as follows. First, regulatory interventions and capital injections are followed by lower levels of liquidity creation. The probability of a decline in liquidity creation increases to up to around 50 percent when such actions are taken. Second, bank risk taking decreases in the aftermath of regulatory interventions and capital injections. Third, while banks' liquidity creation market shares decline over the five years following such disciplinary measures, they also reduce their risk exposure over this period to become safer banks.
Keywords: G21; G28; 330; Liquidity creation; bank distress; regulatory interventions; capital injections; Geldschöpfung; Bankenliquidität; Bankinsolvenz; Bankenpolitik; Öffentliche Kapitalbeteiligung; Deutschland